2010
DOI: 10.1002/cne.22272
|View full text |Cite
|
Sign up to set email alerts
|

Specializations of gastrin‐releasing peptide cells of the mouse suprachiasmatic nucleus

Abstract: The suprachiasmatic nucleus (SCN) of the hypothalamus regulates daily rhythms in physiology and behavior. It is constituted of a heterogeneous population of cells which together form the circuits underlying its master clock function. Numerous studies suggest the existence of two regions that have been termed core and shell. At a gross level, differences between these regions map to distinct functional differences, though the specific role(s) of various peptidergic cellular phenotypes remains unknown. In mouse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Their surgical separation desynchronizes the dorsomedial shell, presumably due to loss of VIPand GRP-ergic signals (29), and a simple model is that core and shell contain reciprocally supportive oscillators coupled by peptidergic signals. Thus, the shell receives a dense innervation by VIP and GRP (30) and expresses VPAC2 (31) and BB2r (26) whereas the V1a receptor is widely distributed across SCN (27). This model complements the conclusion that there is no uniquely specialized or anatomically localized class of cell-autonomous pacemakers (11): rather, AVP, VIP, and other SCN neurons are intrinsic but unstable circadian oscillators that rely on network interactions to stabilize their otherwise noisy cycling.…”
Section: Discussionmentioning
confidence: 76%
“…Their surgical separation desynchronizes the dorsomedial shell, presumably due to loss of VIPand GRP-ergic signals (29), and a simple model is that core and shell contain reciprocally supportive oscillators coupled by peptidergic signals. Thus, the shell receives a dense innervation by VIP and GRP (30) and expresses VPAC2 (31) and BB2r (26) whereas the V1a receptor is widely distributed across SCN (27). This model complements the conclusion that there is no uniquely specialized or anatomically localized class of cell-autonomous pacemakers (11): rather, AVP, VIP, and other SCN neurons are intrinsic but unstable circadian oscillators that rely on network interactions to stabilize their otherwise noisy cycling.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, calbindin-expressing SCN neurons fire action potentials in a rhythmic manner (Jobst and Allen 2002). Similarly, gastrin-releasing peptide (GRP)-expressing neurons do not show a circadian pattern of clock gene expression, suggesting they may not fire action potentials in a circadian pattern (Drouyer et al 2010). The circadian output is the combination of rhythmically and nonrhythmically firing neurons present in individual compartments of the SCN.…”
Section: Scn Neuronal Heterogeneitymentioning
confidence: 99%
“…Breeding parents were homozygote transgenic mice bearing a jellyfish GFP reporter (calbindin-D28K-BAC::GFP transgenic mouse; a generous gift of Dr. N. Heintz, Rockefeller University, New York, NY). We have previously shown that 87% of GFPϩ neurons contain calbindin in 7-day-old pups (Drouyer et al 2010) and 90% of GFPϩ cells contain GRP in the adult (Karatsoreos et al 2004). Here, we have assumed, based on the uniformity of the data set, that all GFPimmunoreactive neurons contain GRP.…”
Section: Animalsmentioning
confidence: 99%
“…They make appositions onto other GRPϩ cells and exhibit dye coupling, suggestive of gap junctions. Dendrites and axons of GRPϩ cells make appositions onto arginine vasopressin (AVP) neurons, whereas the adjacent non-GRP cells have a less extensive fiber network, largely confined to the region of GRPϩ cells (Drouyer et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation